Protective HIV-specific CD8(+) T cells evade T(reg) cell suppression - Elahi, Shokrollah (2011)
Specific human leukocyte antigens (HLAs), notably HLA-B*27 and HLA-B*57 allele groups, have long been associated with control of HIV-1. Although the majority of HIV-specific CD8(+) T cells lose proliferative capacity during chronic infection, T cells restricted by HLA-B*27 or HLAB*57 allele groups do not. Here we show that CD8(+) T cells restricted by 'protective' HLA allele groups are not suppressed by T(ref) cells, whereas, within the same individual, T cells restricted by 'nonprotective' alleles are highly suppressed ex vivo. This differential sensitivity of HIV-specific CD8(+) T cells to T(ref) cell–mediated suppression correlates with their expression of the inhibitory receptor T cell immunoglobulin domain and mucin domain 3 (Tim-3) after stimulation with their cognate epitopes. Furthermore, we show that HLA-B*27– and HLA-B*57–restricted effectors also evade T(ref) cell–mediated suppression by directly killing T(ref) cells they encounter in a granzyme B (GzmB)-dependent manner. This study uncovers a previously unknown explanation for why HLA-B*27 and HLA-B*57 allele groups are associated with delayed HIV-1 disease progression.